PERBANDINGAN SIFAT GELATIN YANG BERASAL DARI KULIT IKAN PATIN (Pangasius hypophthalmus) DAN GELATIN YANG BERASAL DARI KULIT IKAN KOMERSIL - Ira Oktaviani; Fitra Perdana; Azlaini Yus Nasution (JURNAL FARMASI DAN MAKANAN, 2017)
Gelatin is widely used in the food, pharmaceutical, and cosmetic industries. The demand for gelatin increases every year, gelatin derived from pigs and cows is the main source of gelatin in the market. Gelatin that is sourced from other animals such as from poultry and fish is only about 1%. Gelatin from fish becomes a better prospect to develop. Gelatin raw materials can be obtained from the skin, bones, and fish fins. Fish skin is a waste processing of fishery products, such as in the manufacture of meatballs, crackers, and so forth, which has no economic value and even harmful. â€œPatinâ€ catfish is one of the most developed fish due to the high demand from both domestic and international market. Kampar Regency Riau Province is one of the centers of â€œpatinâ€catfish development in Indonesia. Gelatin is valuable for the pharmaceutical and cosmetic industries because it is used in various formulations. This study aims to see the quality of gelatin obtained from catfish skin obtained by acidification process which will be continued utilization as additional material in cosmetic manufacture. In this study, gelatin obtained from â€œpatinâ€ catfish skin extraction was evaluated organoleptically including odor, taste, and shape, moisture content, ash content, pH, and protein contained therein, which results were compared with gelatin derived from commercial fish skins. In organoleptis, the resulting odor is dry powder, odorless, and tasteless, the average water content of commercial fish gelatin is 10.03% and of catatin gelatin is 9.92%, the mean ash content obtained from commercial gelatin fish 2,1958% and â€œpatinâ€ catfish gelatin equal to 0,15%, average protein content on gelatin of commercial fish equal to 85,68% and from â€œpatinâ€ catfish gelatin equal to 88,38%, pH obtained in commercial fish gelatin 6.4 and from â€œpatinâ€catfish gelatin of 5.7.